Jacob's Analytical Assessment in the Evaluation of Arabic Writing Skills at Madrasah Aliyah Negeri Program Keagamaan - Elok Rufaiqoh; Sutaman Sutaman; Zakiyah Arifa; Nahla Ibrahim ElJack Ibrahim; Hasyim Asy’ari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to assess the Arabic writing proficiency of tenth-grade students in the PK 1 class of Madrasah Aliyah Negeri Program Keagamaan (MANPK) Jember through analytical evaluation. The sample comprised 20 students, identified as S1–S20. The data were derived from their in-class compositions titled “Simple Essays,” which were analyzed using Jacobs' Analytical Rubric. This rubric evaluates five key components of writing: content, organization, vocabulary, language use, and mechanics. Employing a quantitative descriptive research design, the findings indicate that the majority of students’ Arabic writing skills fall within the “good to average” category. Specifically, 10% of students performed at the “excellent to very good” level across all aspects, 60% at the “good to average” level, and 30% at the “fair to poor” level—though their vocabulary usage remained at a “good to sufficient” level. These findings provide essential feedback for educators aiming to enhance the teaching and learning of Arabic writing skills.